Formation History of HD 106906 and the Vertical Warping of Debris Disks by an External Inclined Companion - Nathaniel W. H. Moore; Gongjie Li; Lee Hassenzahl; Erika R. Nesvold; Smadar Naoz; Fred C. Adams (The Astrophysical Journal, 2023)
HD 106906 is a planetary system that hosts a wide-orbit companion, as well as an eccentric and flat debris disk, which hold important constraints on its formation and subsequent evolution. The recent observations of the companion constrain its orbit to be eccentric and inclined relative to the plane of the debris disk. Here, we show that, in the presence of the inclined companion, the debris disk quickly (≲5 Myr) becomes warped and puffy. This suggests that the current configuration of the system is relatively recent. We explore the possibility that a recent close encounter with a free-floating planet could produce a companion with orbital parameters that agree with observations of HD 106906 b. We find that this scenario is able to recreate the structure of the debris disk while producing a companion in agreement with observation.